High-durability high-elasticity anti-fouling polyamide fiber and preparation method thereof

CN122898977APending Publication Date: 2026-10-13YIWU HUADING NYLON
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610907944.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-23
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

[0005]本发明旨在提供一种高耐久高弹抗污锦纶纤维及其制备方法,以解决现有技术中锦纶纤维的弹性与抗污性难以兼得、抗污功能不持久、纳米颗粒易脱落以及传统弹性改性方法工艺复杂等技术问题

Benefits of technology

首先是高耐久抗污性能,经测试,所制备的锦纶纤维自然光照射2h后表面油污降解率≥85%;水洗50次后水接触角仍≥138°;拒油等级≥4级;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122898977A_ABST
    Figure CN122898977A_ABST
Patent Text Reader

Abstract

The application discloses a kind of high durability high elastic anti-fouling nylon fiber and its preparation method.The method includes: TiO2 or SiO2 Nanoparticles are activated and modified by silane coupling agent;Caprolactam or nylon 66 salt is copolymerized with amino-terminated polyether block, and then covalently grafted with activated nanopowder, and epoxy crosslinking monomer is added to selectively open the ring and crosslink with the amino group at the end of the polyether soft segment, vacuum devolatilization, and pellet to obtain functional chips;Direct melt spinning is used to adopt two-stage gradient heat drawing, wherein the first-stage high-drawing drives molecular chain orientation and drives nanoparticles to migrate to the surface, and the second-stage low-drawing makes nanoparticles evenly arranged on the surface of the fiber to form a micro-nano double-layer rough structure.The application realizes permanent anchoring of nanoparticles and chemical crosslinking of soft segment by chemical grafting and physical drawing, and the obtained fiber has a water contact angle of ≥138° after 50 times of washing, an oil-repellent of ≥4 levels, an elastic recovery rate retention rate of ≥95%, and a breaking strength of ≥4.2 cN / dtex, and has high durability and anti-fouling as well as permanent high elasticity without spandex.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of polymer materials and fiber manufacturing technology, and more specifically, to a high-durability, high-elasticity, stain-resistant nylon fiber and its preparation method. Background Technology

[0002] Nylon (polyamide) fiber is widely used in clothing, home textiles, and industrial textiles due to its excellent strength, abrasion resistance, and resilience. However, the elastic recovery rate of traditional nylon fiber (especially its elasticity under low stress) is still inferior to that of spandex, and it has poor hydrophobicity and is easily stained with oil. Existing modification techniques, such as blending with nanoparticles or surface coatings, either result in poor spinnability and short-lasting stain resistance due to nanoparticle aggregation, or fail due to coating peeling. More importantly, existing technologies cannot simultaneously resolve the contradiction between "high elasticity" and "durable stain resistance": adding inorganic particles often impairs the mechanical elasticity of the fiber, while improving elasticity may sacrifice the stability of the surface structure.

[0003] To improve the elasticity of nylon, current methods primarily utilize physical blending and bicomponent composite spinning technologies. Physical blending combines nylon filaments or staple fibers with spandex elastic fibers using textile techniques (such as covering, core-spun, and plying). However, this method suffers from issues like fabric aging and complex dyeing processes. Bicomponent composite spinning combines two polymers with different shrinkage properties within the same fiber cross-section. This requires sophisticated composite spinning components and a precise control system, resulting in a complex process and significant equipment investment. Therefore, by altering the structure of the nylon polymer itself (such as through copolymerization modification), the nylon fiber can possess a permanent crimp similar to a spring structure, thus achieving durable elasticity without the need for spandex. This method aims to fundamentally circumvent the durability issues of spandex and the complexity of composite spinning.

[0004] This invention provides a novel nylon fiber that organically combines high elasticity and durable stain resistance, and has a stable structure. Summary of the Invention

[0005] The present invention aims to provide a high-durability, high-elasticity, and stain-resistant nylon fiber and its preparation method, in order to solve the technical problems in the prior art, such as the difficulty in achieving both elasticity and stain resistance of nylon fiber, the lack of long-lasting stain resistance, the easy shedding of nanoparticles, and the complexity of traditional elastic modification methods.

[0006] Specifically, the present invention adopts the following technical solution: A method for preparing a high-durability, high-elasticity, and stain-resistant nylon fiber includes the following steps: Step 1, Functional Nanoparticle Activation and Modification: Select TiO2 or SiO2 nanoparticles with a particle size of 30-80 nm, place them in a 3:1 volume ratio ethanol-deionized water mixed solvent, and prepare a nano-dispersion with a mass fraction of 10%-15%; add 0.8%-1.2% of silane coupling agent KH-550 according to the total mass of the dispersion, ultrasonically disperse for 30-40 min, stir and react at room temperature for 2 h, and after centrifugation, washing, and vacuum drying, obtain functional nanoparticles with surface amino and hydroxyl activated; Step 2, Block copolymerization and graded grafting to prepare functional chips: First, the polymer matrix (caprolactam or nylon 66 salt) is copolymerized with amino-terminated polyether blocks to form a soft and hard segment prepolymer; then it is grafted with functional powder, and finally reacted with epoxy crosslinking monomers to prepare nylon functional chips. Step 3, melt spinning: After drying, the functional chips obtained in Step 2 are directly fed into a single-screw spinning machine with segmented temperature control: Zone 1 240-245℃, Zone 2 245-250℃, Zone 3 250-255℃, and the spinneret box 245-250℃; after the melt is extruded through the spinneret, it is cooled by ring blowing air at a temperature of 35-45℃ and a speed of 0.3-0.5m / s to ensure that the filaments are uniformly solidified to obtain nascent fibers; Step 4, Two-stage gradient thermal stretching and setting: After cooling, the nascent fibers are bundled and oiled, and then subjected to two-stage thermal stretching: the first stage has a stretching ratio of 3.2-3.5 times and a temperature of 145-155℃, driving the molecular chain orientation and causing the grafted nanoparticles to migrate directionally to the fiber surface; the second stage has a stretching ratio of 1.05-1.15 times and a temperature of 130-145℃, completing the thermal setting and making the nanoparticles evenly distributed on the fiber surface, forming a double-layer micro-nano rough structure with micron-level concave and convex and nano-level convex; finally, after low-temperature thermal setting and constant-speed winding, high-durability, high-elasticity, and stain-resistant nylon fiber is obtained.

[0007] Furthermore, the specific steps of step 2 are as follows: (2-1) The polymer matrix is ​​placed into a high-pressure polymerization reactor. The polymer matrix is ​​caprolactam or nylon 66 salt. 4%-8% of the total mass of the polymer matrix is ​​added, along with 2.0%-3.0% of the total mass of the polymer matrix, deionized water, and 0.2% of the total mass of the polymer matrix. After nitrogen purging, a slight positive pressure is maintained. The temperature is raised to 220-230℃ and the pressure is 1.5-1.8 MPa. The reaction is carried out under pressure for 2-2.5 hours to complete the block copolymerization and form a soft and hard segment prepolymer. The composite antioxidant is a mixture of main antioxidant 1098 and auxiliary antioxidant 168 in a mass ratio of 1:1. (2-2) Cool the polymerization reactor to 180-200℃, slowly depressurize to atmospheric pressure, and then heat to 210-230℃; add 0.5%-2.0% of the functional nanopowder obtained in step 1, which is based on the theoretical yield of the polymerization matrix. When actually adding the powder, the yield is calculated by multiplying the mass of the polymerization matrix by the expected yield (95%-98%); stir for 20-30 minutes under atmospheric pressure and nitrogen protection to allow the nanoparticles to covalently graft with the nylon molecular chains. (2-3) After the grafting reaction, add 0.3%-0.6% of epoxy crosslinking monomers according to the total mass of the polymer matrix, and continue to stir the reaction for 15-25 minutes at 210-230℃ and under normal pressure nitrogen protection, so that the epoxy groups can selectively open the ring and crosslink with the terminal amino groups of the polyetheramine soft segment to form intramolecular crosslinking points. (2-4) After the crosslinking reaction is completed, the pressure is gradually reduced to 1000-2000 Pa, and the vacuum is de-vaporized for 30-60 min. Then the vacuum is broken, nitrogen is used to repressurize, the melt is discharged, and it is granulated underwater. The functional nylon chips are obtained by vacuum drying.

[0008] The selective crosslinking mechanism in steps 2-3 is as follows: at the reaction temperature, the epoxy crosslinking monomer preferentially reacts with the aliphatic terminal amino group (the end of the polyether segment, pKa about 9-10), while the reaction rate with the terminal amino group (aromatic or amide ortho position, pKa about 4-5) of the nylon hard segment is slower, thereby achieving selective crosslinking of the soft segment.

[0009] Furthermore, the nanoparticles mentioned in step 1 are 50nm anatase TiO2 nanoparticles, and the amount of silane coupling agent KH-550 added is 1% of the total mass of the dispersion.

[0010] Furthermore, the molecular weight of the amino-terminated polyether in step 2 is 1000-3000; the epoxy crosslinking monomer is selected from one or more of ethylene glycol diglycidyl ether, epichlorohydrin, or bisphenol A type epoxy resin.

[0011] Furthermore, the amount of epoxy crosslinking monomer added in step 2 is 0.4% of the total mass of the polymer matrix.

[0012] Furthermore, in step 2, the absolute pressure of vacuum devolatilization is 1500 Pa, and the devolatilization time is 45 min.

[0013] Furthermore, in step 3, the air temperature of the ring blower cooling is 40℃ and the air speed is 0.4m / s; the temperatures of each section of the spinning process are: zone 1 242℃, zone 2 248℃, zone 3 252℃, and spinneret box 248℃.

[0014] Furthermore, in step 4, the first-stage draw ratio is 3.4 times and the temperature is 150℃, while the second-stage draw ratio is 1.1 times and the temperature is 140℃.

[0015] The nylon fiber prepared by this invention has the following properties: the surface oil degradation rate is ≥85% after 2 hours of natural light irradiation; the water contact angle is ≥138° after 50 washes; the oil repellency grade is ≥4; the elastic recovery rate retention rate is ≥95%; the breaking strength is ≥4.2cN / dtex; the dyeing uniformity is excellent, and the color fastness is grade 4-5.

[0016] After the epoxy crosslinking monomer undergoes ring-opening crosslinking with the terminal amino groups of the polyetheramine soft segment, stable crosslinking points are formed in the nylon molecular backbone, inhibiting long-term slippage of the soft segment and achieving permanent high elasticity without spandex; the functional nanoparticles are covalently grafted with the terminal carboxyl and terminal amino groups of the nylon molecular chain through the amino and hydroxyl groups on the silane coupling agent, preventing particle detachment.

[0017] The above-mentioned solution of the present invention uses the silane coupling agent KH-550 to covalently graft nano-TiO2 or SiO2 onto the nylon molecular chain, solving the problems of easy agglomeration and detachment of nanoparticles in traditional blending or coating methods. Combined with two-stage drawing, the nanoparticles form a stable "micron-level concave-convex + nano-level protrusion" double-layer micro-nano rough structure on the fiber surface, endowing the fiber with superoleophobic and hydrophobic properties. Testing showed that the prepared nylon fiber exhibited a surface oil degradation rate ≥85% after 2 hours of natural light irradiation; a water contact angle ≥138° after 50 water washes; and an oil repellency rating ≥4.

[0018] Secondly, by introducing terminal amino polyethers as soft segments through block copolymerization, and then selectively ring-opening crosslinking between epoxy crosslinking monomers and the terminal amino groups of the polyether soft segments, stable chemical crosslinking points are formed within the molecular chain. This effectively inhibits permanent slippage of the soft segments during repeated stretching, giving the fiber an elastic network structure similar to rubber, while maintaining the crystallinity and strength of the nylon hard segments. After 50 washes, the elastic recovery rate is ≥95%, eliminating the need for spandex or complex composite spinning processes.

[0019] Excellent mechanical and dyeing properties: Because the nanoparticles are anchored by chemical bonds and the cross-linking reaction only targets the soft segments without damaging the crystalline structure of the hard segments of nylon, the fiber's breaking strength can still remain above 4.2 cN / dtex. Simultaneously, the uniform micro-nano structure on the surface facilitates uniform dye adsorption, resulting in excellent dyeing uniformity and a color fastness of 4-5.

[0020] Compared with the prior art, the present invention has the following significant advantages: First, it has high durability and stain resistance. Tests show that the surface oil degradation rate of the prepared nylon fiber is ≥85% after 2 hours of natural light exposure; the water contact angle is still ≥138° after 50 washes; and the oil repellency level is ≥4. Secondly, it has high elasticity. After 50 washes, the elasticity recovery rate is ≥95%, without relying on spandex or complex composite spinning processes. Third, it has excellent mechanical and dyeing properties.

[0021] Meanwhile, the present invention completes block copolymerization, nanografting and crosslinking in the polymerization stage. The resulting chips do not need to be compounded with any masterbatch and can be directly spun. The process is short and the equipment requirements are low, making it suitable for large-scale industrial production. Attached Figure Description

[0022] Figure 1 This is a scanning electron microscope image of the fiber obtained in Example 1 of the present invention.

[0023] Figure 2 This is a comparison chart of the anti-fouling effects of Example 1 of the present invention and conventional nylon.

[0024] Figure 3 This is a scanning electron microscope image of the nylon obtained in Comparative Example 4 of the present invention. Detailed Implementation

[0025] Representative embodiments will now be further refined. It should be understood that the following description is not intended to limit the embodiments to a single preferred embodiment. Rather, it is intended to cover alternatives, modifications, and equivalents that may be included within the substance and scope of the embodiments defined by the appended claims.

[0026] In the following examples, the composite antioxidant used was a mixture of antioxidant 1098 (N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexamethylenediamine) and antioxidant 168 (tris(2,4-di-tert-butylphenyl)phosphite) in a 1:1 mass ratio. The amino-terminated polyether was purchased from Huntsman (JEFFAMINE® series).

[0027] Example 1: Step 1: Activation and modification of functional nanoparticles 50 nm anatase TiO2 nanoparticles were placed in a 3:1 volume ratio ethanol-deionized water mixed solvent to prepare a 12% (w / w) nano-dispersion. 1.0% (w / w) of silane coupling agent KH-550 was added to the dispersion, and the mixture was ultrasonically dispersed for 35 min. The mixture was then stirred at room temperature for 2 h. After centrifugation, washing three times with deionized water, and vacuum drying, TiO2 nanoparticles with activated amino and hydroxyl groups on the surface were obtained.

[0028] Step 2: Preparation of functional slices by block copolymerization and hierarchical grafting (2-1) Caprolactam (polymer matrix) was added to a high-pressure polymerization reactor, along with 6% by weight of terminal amino polyether (molecular weight 2000), 2.5% by weight of deionized water, and 0.2% by weight of composite antioxidant (1098:168=1:1). After nitrogen purging three times, a slight positive pressure (0.05 MPa) was maintained. The temperature was raised to 225°C, and the pressure was increased to approximately 1.6 MPa. The reaction was maintained at this pressure for 2 hours to complete the block copolymerization.

[0029] (2-2) Cool the polymerization reactor to 190°C, slowly depressurize to atmospheric pressure, and then heat it to 220°C. Add 1.8% of the activated TiO2 nanoparticles obtained in step 1, based on the estimated yield of 97% caprolactam. The actual amount added is 1.85% of the mass of caprolactam. Stir for 25 minutes under atmospheric pressure and nitrogen protection.

[0030] (2-3) Add 0.4% of ethylene glycol diglycidyl ether (epoxy crosslinking monomer) of the total mass of caprolactam, and continue stirring the reaction for 20 min at 220℃ and under normal pressure nitrogen protection.

[0031] (2-4) Gradually reduce the pressure to 1500Pa, vacuum devolatilize for 45min, then break the vacuum, repressurize with nitrogen, discharge the melt, cut into pellets underwater, and obtain functional nylon chips by vacuum drying.

[0032] Step 3: Direct melt spinning After the functional chips are dried to a moisture content of ≤0.03%, they are fed into a single-screw spinning machine. Segmented temperature control is used: Zone 1 242℃, Zone 2 248℃, Zone 3 252℃, and the spinneret box 248℃. After the melt is extruded through the spinneret, it is cooled by a ring-blown air system at a temperature of 40℃ and a velocity of 0.4 m / s.

[0033] Step 4: Two-stage gradient thermal stretching and shaping After cooling, the nascent fibers are bundled, oiled, and subjected to two-stage hot stretching: the first stage has a stretch ratio of 3.4 times and a temperature of 150℃; the second stage has a stretch ratio of 1.1 times and a temperature of 140℃. Finally, they are heat-set at a low temperature of 130℃ and wound at a constant speed to obtain high-durability, high-elasticity, and stain-resistant nylon fibers.

[0034] like Figure 1 As shown, the fiber surface obtained in Example 1 formed a uniform bilayer micro-nano rough structure with micron-level bumps (spacing approximately 2-5 μm) and nano-level protrusions (size approximately 50-100 nm). This is mainly due to the movement and migration of polymer chain segments under stress, allowing TiO2 nanoparticles to precipitate more effectively onto the fiber surface, forming a protruding structure similar to a lotus leaf, with no obvious agglomeration of the particles.

[0035] Example 2 The difference from Example 1 is as follows: in step 1, the nanoparticles are 30nm SiO2; in step 2, the terminal amino polyether has a molecular weight of 1000 and is added at 4% of the total mass of the polymer matrix; the epoxy crosslinking monomer is epichlorohydrin and is added at 0.3% of the total mass of the polymer matrix; the functional nanoparticles are added at 0.5% of the total mass of the final fiber. The first-stage draw ratio is 3.2 times and the temperature is 145℃; the second-stage draw ratio is 1.05 times and the temperature is 130℃. Other conditions are the same as in Example 1.

[0036] Example 3 The difference from Example 1 is as follows: in step 1, the nanoparticles are 80nm TiO2; in step 2, the terminal amino polyether has a molecular weight of 3000 and is added at 8% of the total mass of the polymer matrix; the epoxy crosslinking monomer is bisphenol A type epoxy resin (E-51) and is added at 0.6% of the total mass of the polymer matrix; the functional nanoparticles are added at 2.0% of the total mass of the final fiber. The first-stage draw ratio is 3.5 times and the temperature is 155℃; the second-stage draw ratio is 1.15 times and the temperature is 145℃. Other conditions are the same as in Example 1.

[0037] Comparative Example 1 The difference from Example 1 is that no epoxy crosslinking monomer is added in step 2 (i.e., steps 2-3 are omitted), while the other conditions are exactly the same as in Example 1.

[0038] Comparative Example 2 The difference from Example 1 is that the nanoparticles in step 1 are not activated and modified by KH-550, but are added directly in step 2-2 by physical blending, while the other conditions are exactly the same as in Example 1.

[0039] Performance Tests and Results The fibers prepared in Examples 1-3 and Comparative Examples 1-2 were subjected to performance tests, and the results are shown in Table 1.

[0040] Test method: Water contact angle: The average value of 5 different locations was taken using a contact angle measuring instrument; Oil repellency rating: Tested according to AATCC 118 standard; Elastic recovery rate: According to GB / T 14344 standard, the elastic recovery rate is calculated by cyclic stretching at a constant elongation of 30%, and the retention rate after 50 water washes is tested; Fracture strength: in accordance with GB / T 14344 standard; Oil stain degradation rate: Methylene blue-stained oil stains were dropped onto the fiber surface and exposed to natural light for 2 hours. The residue was observed and the degradation area ratio was calculated. Color fastness: according to GB / T 3921 (wash fastness) and GB / T3920 (rub fastness) standards.

[0041] Table 1: Performance Comparison of Examples and Comparative Examples The data in the table above shows that: Examples 1-3 all achieved excellent stain resistance and durability (contact angle ≥138° after 50 washes), high elastic recovery rate and retention rate (≥95%), as well as good mechanical and dyeing properties.

[0042] The elastic recovery rate and water washing retention rate of Comparative Example 1 (without chemical crosslinking) decreased significantly, indicating that chemical crosslinking is the key to achieving "permanent high elasticity".

[0043] The antifouling performance (contact angle, oil repellency level) of Comparative Example 2 (nanoparticles not covalently grafted, only physically blended) was acceptable initially, but dropped sharply after washing, and the degradation rate and strength decreased, indicating that physical blending cannot solve the performance degradation problem caused by nanoparticle shedding and agglomeration.

[0044] In addition, infrared spectroscopy analysis (FT-IR, KBr pellet) was performed on the fibers of Example 1 at 1650 cm⁻¹. -1 (Amide I band) and 1560cm -1 In addition to the (amide II band), a length of 1100 cm appeared. -1 The nearby Si-OC characteristic absorption peak (from the bonding between KH-550 and nano-TiO2 and nylon end groups), and 920 cm⁻¹ -1 The COC absorption peak formed after the nearby epoxy ring-opening confirms the occurrence of covalent grafting and cross-linking reactions.

[0045] Furthermore, comparing Example 1 with conventional nylon fibers, the stain resistance comparison chart shows that the nylon prepared in Example 1 of this invention has a significant stain resistance effect, while conventional fibers, due to the absence of the aforementioned additives, cannot form stain resistance on the fiber surface. Figure 1 The surface structure, resembling a lotus leaf, does not provide any anti-fouling effect.

[0046] To demonstrate that the polymerization effect of the present invention is even better, TiO2 is coated onto chemically textured nylon fibers using a finishing method following the steps below.

[0047] Comparative Example 4: This method includes the following steps: (1) Add sufficient nylon 66 salt solution to a high-pressure polymerization reactor. Add 8 kg of polyethylene glycol as a flexible segment and a small amount of acetic acid as an end-blocking agent. Increase the temperature and pressure under nitrogen protection. First, maintain the pressure at 220℃ and 1.8 MPa for 2 hours, then slowly increase the temperature to 280℃, and slowly depressurize to atmospheric pressure during this process. React at 280℃ under vacuum conditions (absolute pressure < 100 Pa) for 1 hour to ensure complete reaction. Discharge, pelletize, and dry to obtain high-elasticity nylon copolymer chips; (2) The high-elasticity nylon copolymer chips are fed into the spinning machine. The screw temperature is set as follows: Zone 1 275℃, Zone 2 285℃, Zone 3 290℃, and the chamber temperature 285℃. (3) The melt is extruded through a spinneret, with a cooling air temperature of 20°C and an air velocity of 0.4 m / s. The nascent fibers are oiled and then subjected to two stages of drawing. First stage drawing: drawing ratio 3.5 times, drawing temperature 160°C. Second stage drawing: drawing ratio 1.2 times, drawing temperature 180°C. The high-elasticity nylon fiber of the present invention is obtained by winding. (4) Disperse TiO2 nanoparticles in a solution and coat them onto the surface of the high-elastic nylon fiber prepared in step (3) by post-treatment to obtain stain-resistant high-elastic nylon fiber.

[0048] Depend on Figure 3 It can be seen that although TiO2 particles were successfully coated onto the surface of nylon fibers through post-treatment coating, the distribution of TiO2 particles was obviously uneven and the aggregation was serious. This will make it easier for the particles to fall off during later use, resulting in poor water resistance and durability of the fibers.

[0049] It will be apparent to those skilled in the art that modifications, combinations, and variations can be made to the teachings described above.

Claims

1. A method for preparing a high-durability, high-elasticity, stain-resistant nylon fiber, characterized in that: Includes the following steps: Step 1, Functional Nanoparticle Activation and Modification: Select TiO2 or SiO2 nanoparticles with a particle size of 30-80 nm, place them in a 3:1 volume ratio ethanol-deionized water mixed solvent, and prepare a nano-dispersion with a mass fraction of 10%-15%; add 0.8%-1.2% of silane coupling agent KH-550 according to the total mass of the dispersion, ultrasonically disperse for 30-40 min, stir and react at room temperature for 2 h, and after centrifugation, washing, and vacuum drying, obtain functional nanoparticles with surface amino and hydroxyl activated; Step 2, Block copolymerization and graded grafting to prepare functional chips: First, the polymer matrix is ​​copolymerized with amino-terminated polyether block copolymers to form soft and hard segment prepolymers; the polymer matrix is ​​caprolactam or nylon 66 salt; then it is grafted with functional powders, and finally reacted with epoxy crosslinking monomers to prepare nylon functional chips. Step 3, melt spinning: After drying, the functional chips obtained in Step 2 are directly fed into a single-screw spinning machine with segmented temperature control: Zone 1 240-245℃, Zone 2 245-250℃, Zone 3 250-255℃, and the spinneret box 245-250℃; after the melt is extruded through the spinneret, it is cooled by ring blowing air at a temperature of 35-45℃ and a speed of 0.3-0.5m / s to ensure that the filaments are uniformly solidified to obtain nascent fibers; Step 4, Two-stage gradient thermal stretching and setting: After cooling, the nascent fibers are bundled and oiled, and then subjected to two-stage thermal stretching: the first stage has a stretching ratio of 3.2-3.5 times and a temperature of 145-155℃, driving the molecular chain orientation and causing the grafted nanoparticles to migrate directionally to the fiber surface; the second stage has a stretching ratio of 1.05-1.15 times and a temperature of 130-145℃, completing the thermal setting and making the nanoparticles evenly distributed on the fiber surface, forming a double-layer micro-nano rough structure with micron-level concave and convex and nano-level convex; finally, after low-temperature thermal setting at 100-140℃ and constant-speed winding, high-durability, high-elasticity, and stain-resistant nylon fiber is obtained.

2. The preparation method according to claim 1, characterized in that: The specific steps of step 2 are as follows: (2-1) The polymer matrix is ​​put into a high-pressure polymerization reactor. The polymer matrix is ​​caprolactam or nylon 66 salt. 4%-8% of the total mass of the polymer matrix is ​​added, along with 2.0%-3.0% of the total mass of the polymer matrix, deionized water, and 0.2% of the total mass of the polymer matrix. After nitrogen purging, a slight positive pressure is maintained. The temperature is raised to 220-230℃ and the pressure is 1.5-1.8 MPa. The reaction is carried out under pressure for 2-2.5 hours to complete the block copolymerization and form a soft and hard segment prepolymer. (2-2) Cool the polymerization reactor to 180-200℃, slowly depressurize to atmospheric pressure, and then heat to 210-230℃; add 0.5%-2.0% of the functional nanoparticles obtained in step 1, and stir for 20-30 minutes under atmospheric pressure nitrogen protection to allow the nanoparticles to covalently graft with the nylon molecular chains. (2-3) After the grafting reaction, add 0.3%-0.6% of epoxy crosslinking monomers according to the total mass of the polymer matrix, and continue to stir the reaction for 15-25 minutes at 210-230℃ and under normal pressure nitrogen protection, so that the epoxy groups can selectively open the ring and crosslink with the terminal amino groups of the polyetheramine soft segment to form intramolecular crosslinking points. (2-4) After the crosslinking reaction is completed, the pressure is gradually reduced to 1000-2000 Pa, and the vacuum is de-vaporized for 30-60 min. Then the vacuum is broken, nitrogen is used to repressurize, the melt is discharged, and it is granulated underwater. The functional nylon chips are obtained by vacuum drying.

3. The preparation method according to claim 1, characterized in that: The nanoparticles mentioned in step 1 are 50nm anatase TiO2 nanoparticles, and the amount of silane coupling agent KH-550 added is 1% of the total mass of the dispersion.

4. The preparation method according to claim 1, characterized in that: The terminal amino polyether in step 2 has a molecular weight of 1000-3000; the epoxy crosslinking monomer is selected from one or more of ethylene glycol diglycidyl ether, epichlorohydrin, or bisphenol A type epoxy resin.

5. The preparation method according to claim 1, characterized in that: The amount of epoxy crosslinking monomer added in step 2 is 0.4% of the total mass of the polymer matrix.

6. The preparation method according to claim 1, characterized in that: In step 2, the absolute pressure of vacuum devolatilization is 1500 Pa, and the devolatilization time is 45 min.

7. The preparation method according to claim 1, characterized in that: In step 3, the air temperature of the ring blower cooling is 40℃ and the air speed is 0.4m / s; the temperatures of each section of the spinning process are: zone 1 242℃, zone 2 248℃, zone 3 252℃, and spinneret box 248℃.

8. The preparation method according to claim 1, characterized in that: In step 4, the first-stage draw ratio is 3.4 times and the temperature is 150℃, while the second-stage draw ratio is 1.1 times and the temperature is 140℃.

9. A high-durability, high-elasticity, stain-resistant nylon fiber prepared by the preparation method according to any one of claims 1-8.